Eduwisata sebagai Model pengembangan Wisata yang Berorientasi pada Pendidikan dan Kesadaran lingkungan di Hutan Mangrove Karangsong Indramayu-Indonesia - Sudirman, Sudirman; Rahayuningsi, Margareta; Marianti, Aditya (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Background: Mangrove forests are very important coastal ecosystems because they provide various benefits, including providing shelter for various biological species, protecting beaches from abrasion, and storing carbon. The potential of the Karangsong mangrove forest, which is an integrated area, is very important for tourism growth, especially sustainable natural tourism. This potential also functions as a means to improve education and environmental preservation, as well as as an economic resource. An approach that may be effective is to integrate education and tourism, or what is known as